The Effectiveness Of Between Leaves Booked Water For Overcoming Leucorrhoea In Grade X Adolescents At Hafsyah Medan Health Vocational School In 2021 - Maulina Mawaddah; Eka Sylviana Siregar (Science Midwifery, 2022)
Reproductive organs are organs that are sensitive and require special care. The health of the reproductive organs begins with maintaining personal hygiene, including keeping the vagina clean, healthy, normal and free from disease. One of the reproductive health problems in young people is vaginal discharge (flour albus). The purpose of the study was to determine the effectiveness of betel leaf boiled water to treat vaginal discharge in class X adolescents at the Hafsyah Health Vocational School in Medan in 2021. This type of research was a pre-experimental design study with the one group pretest-post test method. The results of the study Before being given boiled water of betel leaf there were the majority of teenagers who experienced vaginal discharge with an abnormal scale of 20 0rang respondents (100%). After being given boiled water of betel leaf, there were the majority of teenagers with a normal scale of 20 respondents (100%). The T test was carried out in the control group before being given boiled water for betel leaves and after being given boiled water for betel leaves, there was a value of -2.517 with a p-value of 0.021. So it can be concluded that there is an effect of betel leaf boiled water to overcome vaginal discharge in class X adolescents at SMK Kesehatan Hafsyah Medan, with a T test result of -2.517 and a p value of 0.021.